2002
DOI: 10.1034/j.1399-3054.2002.1140107.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of asparagine synthetase in rice (Oryza sativa) roots in response to nitrogen

Abstract: The expression of asparagine synthetase (AS; EC 6.3.5.4) in response to externally supplied nitrogen was investigated with respect to enzyme activity and protein levels as detected immunologically in rice (Oryza sativa) seedlings. The asparagine content was very low in leaves and roots of nitrogen-starved rice plants but increased significantly after the supply of 1 mM NH4+ to the nutrient solution. While neither AS activity nor AS protein could be detected in leaves and roots prior to the supply of nitrogen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
2
15
0
1
Order By: Relevance
“…Asparagine synthesis is enabled by both the stimulation of dark carbon fixation (Ikeda et al . 1992) and the expression of asparagines synthetase (Kawachi et al . 2002) when ammonium concentrations are high in the roots of leguminous plants.…”
Section: Discussionmentioning
confidence: 99%
“…Asparagine synthesis is enabled by both the stimulation of dark carbon fixation (Ikeda et al . 1992) and the expression of asparagines synthetase (Kawachi et al . 2002) when ammonium concentrations are high in the roots of leguminous plants.…”
Section: Discussionmentioning
confidence: 99%
“…Both enzymes are located in plastids in root cells. 15 N-labeling of asparagine from 15 N-ammonium occurs steadily in the rice roots (Yoneyama and Kumazawa, 1974), and this is probably catalyzed by the glutamine-dependent asparagine synthetase 1 (OsAS1, EC 6.3.5.4; Kawachi et al, 2002; Ohashi et al, 2015). When rice seedlings were treated with 15 N-labeled ammonium sulfate, a rapid labeling of glutamine and a steady labeling of asparagine were detected in the xylem exudates (Yoneyama, 1986).…”
Section: Current Knowledge On the Uptake Assimilation And Transportmentioning
confidence: 99%
“…Radish roots treated with 6 mM ammonium for 7 d contained four times more glutamine than asparagine (Ota and Yamamoto 1990). Magalhaes et al (1995) reported that maize roots contained almost the same amount of asparagine as glutamine when maize plants were grown on 10 mM ammonium media for 10 d. In barley and rice roots, the asparagine content was only slightly lower than the glutamine content and the content of both amides increased significantly after the supply of ammonium to the nutrient solution (Rigano et al 1996;Kawachi et al 2002). Amide synthesis in maize and rice roots seems to be similar to that in wheat roots compared to tomato roots because of the high proportion of asparagine among root soluble amino acids of such plants.…”
Section: Discussionmentioning
confidence: 99%
“…These results coincide with those of the amide synthesis from glucose in tomato and wheat roots. Kawachi et al (2002) reported that the asparagine synthetase activity increased in rice roots by the supply of ammonium nitrogen. It is thus considered that the enhancement of the asparagine synthetase activity might be larger in wheat roots than in tomato roots.…”
Section: Discussionmentioning
confidence: 99%